Gender in Peacebuilding : Local Practices in Indonesia and Nigeria - Prügl, Elisabeth; Onyesoh, Joy; Kunz, Rahel; Myrttinen, Henri; Rahmawati, Arifah; Udasmoro, Wening; Achakpa, Mimidoo; Rigual, Christelle (International development policy, 2021)
Gender, age, class, ethnicity, religion, and political ideologies all matter in peacebuilding. Adopting a feminist approach, the 13th volume of International Development Policy analyses such intersecting differences in local contexts to develop a better understanding of how intersectionally gendered dynamics shape and are shaped by peacebuilding. In this volume, findings are presented from a six-year collaborative research project that, involving scholars from Indonesia, Nigeria, and Switzerland, investigated peacebuilding initiatives in Indonesia and Nigeria. The authors identify a number of logics that highlight how gender is deployed strategically or asserts itself inadvertently through gender stereotypes, gendered divisions of labour, or identity constructions. Contributors include: Mimidoo Achakpa, Ceren Bulduk, Rahel Kunz, Henri Myrttinen, Joy Onyesoh, Elisabeth Prügl, Arifah Rahmawati, Christelle Rigual and Wening Udasmoro.